Pengaruh Ekuitas Merek, Kelompok Rujukan Dan Preferensi Merek Terhadap Keputusan Memilih Program Studi Manajemen Fakultas Ekonomi Dan Bisnis Universitas Islam Malang - Yuni Asmayunita; N Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to determine the effect of brand equity, reference groups and brand preferences simultaneously and partially on the decision to choose a management study program at FEB Unisma. The population using management students of FEB Unisma TA class 18/19 & TA 19/20 known numbers are recorded at the Education Ministry as many as 6,412 students. Determination of the research sample using purposive sampling techniques that have been calculated using the Slovin formula totaling 99 respondents. Analysis using multiple linear regression models. The results of this study indicate that brand awareness is partially significant influence on decision making, brand association partially influences decision making, impression of brand quality partially on decision making, brand loyalty partially on decision making, reference group partially on decision making, and Brand preference partially influences significantly on the decision of choosing. Simultaneously the results of this study are brand awareness, brand association, brand quality impression, brand loyalty, reference groups and brand preferences significantly influence the decision to choose a management study program at FEB Unisma. Keywords: brand awareness, brand association, brand quality impression, brand loyalty, reference groups, brand preferences and decision to choose